RESOURCES OF UNDERGROUND GEOLOGICAL SPACE OF UKRAINE - KORNIEIENKO, S.; KORBUTIAK, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The resources of underground geological space of Ukraine are examined and the problems of underground building and use of underground objects are analysed. It is set that the intensive economic mastering of the ground geological space of Ukraine created the very sharp deficit of free earths and that in such terms, building and use of underground objects acts important part in two main aspects: from one side this freeing of resources of the ground space and his ecological cleanness, and from other – dangerous geological processes which did not appear before at the ground building activate during building of underground objects.